Testing of Technology Acceptance Model on Core Banking System: A Perspective on Mandatory Use - Ambodo, Burhan Suryo; Suryanto, Rudy; Sofyani, Hafiez (Jurnal Dinamika Akuntansi, 2017)
This study aims to examine the acceptance of Core Banking System (CBS) which is mandatory use software. The objects of this research are teller, customer service, and back office Branch of Bank BPD DIY Wonosari. Data were measured using Likert scale in five range value. A number of 49 data were analyzed using Partial Least Square (PLS). The results showed that ease of use had no positive effect on symbolic adoption; attitudes toward usage and perceived conformance has a positive effect on symbolic adoption, ease of use and perceived compatibility has no effect on attitudes towards usage. Usability, satisfaction and compatibility that are felt to positively affect attitude toward usage. In the information technology model that is mandatory use, it is important to note the symbolic adoption of information technology therefore the performance of the user (employee/employee) can remain good. In particular for banking institutions that using CBS, it is important to improve the use of CBS, user satisfaction and CBS conformity with business processes, given the current banking business processes that are constantly expanding, there is no possibility of adjusting CBS to business processes at later.